(De-)assetizing pharmaceutical patents: Patent contestations behind a blockbuster drug. Issue 1 (2nd January 2022) - Bourgeron, Théo; Geiger, Susi
Abstract: Recent debates in public health and social sciences have shown how biofinancialization has been fuelled by patents' transformation into 'patent-as-assets'. This paper traces the historical construction of one such patent-as-asset bundle: the multi-billion worth architecture of patents behind the hepatitis C blockbuster drug sofosbuvir. Following this process from the late 1980s to present times, we highlight the ontological entanglements of pharmaceutical patents and the scientific, legal, commercial and political contestations that result from the focal firms' assetization projects. By shining a light on these entanglements, our paper points to the extraordinary historical conditions required for the assetization of drug patents as well as to their vulnerability to contestations. In particular, we highlight new forms of patent activism that threaten the 'asset condition' of high-priced pharmaceuticals.